Magnitude of mortality and associated factors among road traffic accident victim children admitted in East and West Gojjam Zone specialized public hospitals Northwest, Ethiopia - Amanuel Taye; Tilksew Ayalew; Balew Zeleke; Agegnehu Bante; Addisu Endale (BMC Pediatrics)
Abstract Background A road traffic accident is a collision between vehicles, between pedestrians and vehicles, between vehicles and animals, or between fixed obstacles and vehicles that leads to fatal human injury and premature death. Children are highly vulnerable to road traffic accident death. Yet, evidence is scarce concerning it in this study area. This study aimed to determine the magnitude of mortality and associated factors among road traffic accident victim children. Methods An institution-based cross-sectional study was conducted among 391 victimized children using simple random sampling techniques from March 1st, 2021, to April 30th, 2021. The sample size was calculated using a single population proportion formula, and the data were collected retrospectively using a structured checklist. The data were checked for completeness and consistency, coded, entered into EPI Data version 3.1, and then transferred to STATA version 14 statistical software for analysis. Bivariate and multivariable binary logistic regression analyses were conducted to identify the association between dependent and independent variables. An adjusted odds ratio with a 95% CI was used to measure the strength of the association, and a P-value ≤ 0.05 was considered statistically significant. Result The overall mortality was 10.7% (95% CI: 8- 14). Patients’ age within 1- 4 years (AOR (95%CI: 7(2.0–24.6)), urgent need of blood transfusion (AOR (95%CI: 3.2(1.03–9.8)), Glasgow coma scale < 8 (AOR (95%CI: 6.7(2.1–20.8)), surgery done (AOR (95%CI: 4.7(1.6–14.1)), and length of stay < 5 days (AOR (95%CI: 4.7(1.6–13.3)) were significantly associated with mortality of road traffic accident victim children. Conclusion The overall mortality was high compared with other countries’ findings. Being young, in urgent need of blood transfusion, Glasgow coma scale < 8, undergoing surgery, and short length of stay were significantly associated with mortality of road traffic accident victim children. This study recommended prioritizing young children and timely blood transfusions for emergency cases.